Prostaglandin E2, prostaglandin I2 and the vascular changes of inflammation. - Williams, T J (1979)
1. Plasma exudation and blood flow changes induced by intradermal injection of prostaglandins E2 (PGE2), I2 (PG12), D2 (PGD2) and F2 alpha (PGF2 alpha) were measured in rabbit dorsal skin by the use of [131I]-albumin and 133Xe. 2. Little plasma exudation was produced by any of the prostaglandins when injected alone. 3. Both PGE2 and PGI2 were potent at increasing blood flow, whereas PGF2 alpha and PGD2 produced an increase only at high doses. 4. All of the prostaglandins studied potentiated the plasma exudation induced by bradykinin. PGE2 and PGI2 had similar potent potentiating activity, whereas PGD2 and PGF2 alpha had activity at doses too high to be of biological significance. 5. Intradermal injections of arachidonate alone resulted in little plasma exudation but produced an increase in blood flow. Arachidonate potentiated bradykinin-induced plasma exudation. 6. Locally-injected indomethacin had no effect on basal blood flow and little effect on the exudation produced by bradykinin, but indomethacin did inhibit the vasodilatation and exudation potentiation produced by arachidonate. 7. PGE2 and PGI2 had similar potency in producing marked potentiation of plasma exudation induced by intradermal injection of zymosan. 8. In the reaction to zymosan, it is concluded that vasodilatation is the result of the release of arachidonate, which is subsequently coverted to either PGE2 or PGI2. These substances regulate the plasma exudation induced by independently-released vascular permeability-increasing mediators.